Pengaruh PPN, PKB Tarif Progresif, dan Pendapatan WP pada Daya Beli Konsumen Kendaraan Bermotor - Bella Lestari, I G. A.; Yenni Latrini, Made (E-Jurnal Akuntansi, 2020)
Consumer purchasing power can be influenced by several factors, especially when purchasing motor vehicles is the existence of VAT and Progressive PKB rates that are imposed when buying a motorized vehicle. This study aims to review the imposition of VAT, PKB Progressive Rates, and WP income on consumer purchasing power for the purchase of motor vehicles. The research took place in the SAMSAT office with the city of Denpasar. This study amounted to 100 respondents. Multiple linear regression is an analysis technique used in this study. Referring to the results of the analysis found that the effect of value added tax and income WP has a significant influence on purchasing power. Whereas progressive tariff PKB does not influence consumer purchasing power. This research confirms the theory of the principle of purchasing power and the theory of prestige. Keywords: VAT; Motor Vehicle Tax with Progressive Rates; Taxpayer Income; Purchasing Power.